Who does technology serve? A critical analysis of sociocultural factors shaping opportunities, practices and barriers faced by a smallholders in south-western Colombia - Ramos, Marcela; Triana Ángel, Natalia; Burkart, Stefan; Gutiérrez, Jhon Freddy; Gutierrez Zapata, Diana Maria; Ruden, Alejandro; Sepúlveda, Lady; Barret, Brian (Bristol University Press, 2024)
This article offers a critical approach towards adopting new technologies as a mitigation strategy. It provides a comprehensive analysis that helps illuminate the adoption process and the sociocultural factors intersecting and informing it. Using a capability approach lens and qualitative and participatory data collection methods, this study presents and analyses the testimonies of smallholders living on Colombia’s Pacific coast, currently exposed to a series of interventions that promote changes in production decisions to contribute to reducing national greenhouse gas emissions. Specifically, improved forages, silvopastoral systems and new practices, such as the implementation of rotational pasturing, have been promoted as relevant new approaches. The results show that access to new technologies generates new capabilities, for instance the ability to plan for the challenges imposed by climate change or to develop new strategies to allow the soil to recover naturally. However, these new possibilities are unevenly distributed, creating disadvantages for groups that generally experience conditions of vulnerability, such as young farmers and women. The testimonies also show that many of the promoted initiatives emphasise the need for adaptation and change on the part of smallholders without considering the limitations of technology, the gender issues that affect the inclusion of women and the dynamics that set barriers to young smallholders due to economic restrictions or power issues. Therefore, the study contends that, when understanding technology adoption, it is not only a question of what farmers do or do not do but of what they can be and do in increasingly demanding contexts.